303 IMPACT OF LEAD POSITION IN THE TRICUSPID ANULUS ON THE DEVELOPMENT OF CARDIAC IMPLANTABLE ELECTRONIC DEVICES RELATED TRICUSPID REGURGITATION. (15th December 2022) - Gitto, Mauro; Fazzari, Fabio; Del Monaco, Guido; Monaco, Maria Lo; Lisi, Costanza; Regazzoli, Damiano; Frontera, Antonio; Reimers, Bernhard; Monti, Lorenzo; Francone, Marco; Mangieri, Antonio; Colombo, Antonio; et al.
Abstract: Introduction: Originally considered as the "forgotten valve disease", tricuspid regurgitation (TR) has recently been shown to correlate with consistent morbidity and mortality, suggesting the need for a deeper understanding of its natural course. Direct injury from Cardiac Implantable Electrical Device (CIED) leads is one of the most common causes of primary TR, with a prevalence up to 40%. The aim of the present proof-of-concept study was to evaluate the effect of CIED right ventricular (RV) lead position within the tricuspid anulus on TR development. Methods: Consecutive patients undergoing CIED implantation at our institution (Humanitas Research Horpital IRCCS, Milan, Italy) were included, as long as they had been performed pre- and post- transthoracic echocardiogram (TTE) and a chest CT scan after the implantation. TTE and CT images were retrospectively reviewed. TR severity was graded using a pre-specified 4-class grading scheme: mild, moderate, severe and massive. CIED RV lead position was defined as postero-septal, antero-septal or antero-posterior, based on the commissure in which the lead was observed on a cross-sectional view of the tricuspid anulus at CT scan. Results: 64 patients undergoing CIED implantation from January 2015 to December 2021 were included. All CT scans were non-ECG gated. TR was detected in 42 patients (65.62%) at pre-implantation TTE. The RV lead was implanted across the postero-septal, antero-posterior and antero-septal commissures in 35 (54.7%), 16 (25%) and 13 (20.3%) patients respectively. After the implantation, 12 individuals (18.75%) had new-onset or worsening TR, with CIED lead contributing to TR in 46.88% of cases (30/64), and 26 (40.63%) had worse RV function. At logistic regression analysis, the absence of atrial fibrillation was the only independent predictor of new-onset or worsening TR (OR: 0.17, 95% CI: 0.03-0.86, p=0.032), while CIED RV lead in the postero-septal commissure was associated with a numerically lower risk as compared to other sites (OR: 0.34, 95% CI: 0.09-1.27, p=0.108). Consistently, the degree of increase in TR severity was numerically lower in patients with a lead in the postero-septal commissure (Δ = 0.38±0.10 vs. 0.63±0.13, p=0.07). Conclusions: CIED implantation is associated with increasing TR severity and worsening RV function. Positioning a lead across the postero-septal commissure of the tricuspid anulus might have a lower impact on TR development and worsening, thus representing a feasible option to prevent CIED-related TR.